Coarse-grained molecular dynamics simulations of biomolecules - Ken Takahashi; Takayuki Oda; Keiji Naruse (AIMS Biophysics, 2014)
Coarse-grained molecular dynamics (CGMD) simulations are increasingly being used to analyze the behaviors of biological systems. When appropriately used, CGMD can simulate the behaviors of molecular systems several hundred times faster than elaborate all-atom molecular dynamics simulations with similar accuracy. CGMD parameters for lipids, proteins, nucleic acids, and some artificial substances such as carbon nanotubes have been suggested. Here we briefly discuss a method for CGMD system configuration and the types of analysis and perturbations that can be performed with CGMD simulations. We also describe specific examples to show how CGMD simulations have been applied to various situations, and then describe experimental results that were used to validate the simulation results. CGMD simulations are applicable to resolving problems for various biological systems.